IMPROVING PASSENGERS SATISFACTION OF “TRAVEL” CORRIDOR PADANG-PESISIR SELATAN USING IMPORTANCE - SATISFACTION ANALYSIS (ISA) - Yosritzal Yosritzal; Seprino Hendra; Bayu Martanto Adji (Universitas Mercu Buana, 2019)
This study was motivated by the case of the disappearance of legal bus services due to their loss in competition with a kind of car services called “Travel” for the corridor of Padang - Pesisir Selatan, West Sumatera, Indonesia. Travel might not legal public transport services, and therefore, in this study is also called un-official public transportation. This study aims to determine the driving attributes for passenger’s satisfaction of un-official public transportation services and to figure out the service attributes that need to be improved according to passengers’ perceptions. Data was collected using random sampling with a total sample of 160 respondents and was analyzed using the Importance Satisfaction Analysis (ISA) method. Quadrant analysis of ISA revealed that the availability of music and air conditioner on-board is not so essential but resulting a higher satisfaction to passengers. Passengers are calling for an improvement of the services by consistently implementing the law against a driver who uses a mobile phone while driving or driving inconsiderately, and improving the courtesy and friendliness of the driver.